2017
DOI: 10.1007/s11934-017-0686-7
|View full text |Cite
|
Sign up to set email alerts
|

The Dilemma of Adolescent Varicoceles: Do They Really Have to Be Repaired?

Abstract: The primary indication for varicocele repair in adults, that of failed paternity, must be substituted in the adolescent population with surrogate parameters of testicular size differential and semen analysis. Making recommendations based on these two parameters is incredibly difficult because studies often have contradictory findings, different patient populations, and lack of long term follow up of the key endpoint, paternity. Therefore, it is not a surprise that recommendations for adolescent varicocele repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
1
11
0
2
Order By: Relevance
“…In pre-pubertal individuals, prevalence of varicocele in is low (<1% in boys under 10 years) 3 and increases during puberty to a prevalence of 15%, which is similar to that seen in adults 5 . Akbay et al 6 evaluated varicocele in 4092 boys aged 2-19 observing varicocele prevalence of < 1% in boys 2-10, 7.8% in boys between 11-14 and 14.1% in boys between 15-19 years old.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…In pre-pubertal individuals, prevalence of varicocele in is low (<1% in boys under 10 years) 3 and increases during puberty to a prevalence of 15%, which is similar to that seen in adults 5 . Akbay et al 6 evaluated varicocele in 4092 boys aged 2-19 observing varicocele prevalence of < 1% in boys 2-10, 7.8% in boys between 11-14 and 14.1% in boys between 15-19 years old.…”
Section: Introductionsupporting
confidence: 56%
“…Previous studies by Diamond et al 38 and Mori et al 39 demonstrated lower sperm concentrations and lower progressive motility. Diamond et al 5 also reports correlation between testicular asymmetry and decrease in total motile count. Correlation between semen parameters and varicocele grade has not been established 5 .…”
Section: Seminal Analysis and Hormonal Evaluationmentioning
confidence: 92%
See 3 more Smart Citations